SEJARAH BERDIRINYA PERGURUAN RAKYAT (VOLKSUNIVERSITEIT) 1928 DI JAKARTA - Putut Wisnu Kurniawan (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2017)
This research aims to description and analysis about the historical of Perguruan Rakyat School (Volksuniversiteit) in Jakarta (1928). The research of this special issue of  the  historical base of Perguruan Rakyat. This study in order to critical history method there are 5 steps such as: (1)  Topic selection, this is first step in a research to certain issue will investigates,    (2)Heuristic, this is step to assembling  the historical sources, (3) Critical Source, it is the research of tracks or historical source which assembling so we found the authentic source and accurate, (4) Interpretation, this is the analysis of historical sources where it accociated and verificated, (5) Historigraphy, this is to telling of synthesis from chronological research. The results of this research are: First, Perguruan Rakyat builded the base of Sumpah Pemuda and the effect from ethical-policy decisions. Second, appear of nationalism is base to offering the understand for societies. Third, education is the  effective step to offering the nationalism concept for societies. And Finally, the figures are the graduated of Perhimpunan Indonesia